Polylactic acid composite material as well as preparation method and application thereof
By adding talc and PBS to polylactic acid and controlling its end carboxyl groups and polydispersion coefficient, a polylactic acid composite material with excellent humidity and heat aging resistance was prepared, which solved the aging problem of polylactic acid under high temperature and high humidity conditions and was suitable for the preparation of tableware and other products.
Patent Information
- Application Number
- CN202510416061.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-03
- Publication Date
- 2025-07-04
AI Technical Summary
The existing polylactic acid materials have poor aging performance under high temperature and high humidity conditions, which limits their wide application.
Polylactic acid composite materials are prepared by adding a specific amount of talc and polybutylene succinate (PBS) to polylactic acid and controlling the end carboxyl content and polydispersion coefficient of polylactic acid within a specific range.
After aging of polylactic acid composite materials at 85°C and 85% humidity for 6 hours, the tensile strength retention rate exceeds 60%, making them suitable for products with high requirements for moisture and heat aging resistance.
Smart Images

Figure BDA0005343977110000051 
Figure BDA0005343977110000062 
Figure BDA0005343977110000071
Abstract
Description
Technical Field
[0001] This application relates to the field of polymer materials, and particularly relates to a polylactic acid composite material, a preparation method thereof, and an application thereof. Background Art
[0002] Starch-rich corn can be processed by modern biotechnology to produce a colorless and transparent liquid - lactic acid. Through a special polymerization reaction process, lactic acid can generate granular polymer material polylactic acid (PLA). PLA has the best tensile strength and ductility and can be produced by various common processing methods, such as: melt extrusion molding, injection molding, blown film molding, foam molding, and vacuum molding, etc. However, at present, the large-scale popularization and application of PLA as a general-purpose plastic are still restricted to a certain extent. This is mainly because the aging resistance of PLA is poor. For example, under the simulated accelerated aging reaction conditions of a temperature of 85°C and a humidity of 85%, its properties, such as tensile strength, decline too fast to be used. Therefore, how to improve the aging resistance of polylactic acid is an issue that must be solved in expanding the application of polylactic acid. Summary of the Invention
[0003] Based on the defects existing in the prior art, the purpose of this application is to provide a polylactic acid composite material, a preparation method thereof, and an application thereof, and the obtained polylactic acid composite material has excellent resistance to humid heat aging.
[0004] To achieve the above purpose, in the first aspect, this application provides a polylactic acid composite material, which comprises the following components in parts by weight:
[0005] Polylactic acid 54 - 91 parts,
[0006] Talc powder 10 - 45 parts,
[0007] Polybutylene succinate (PBS) 1 - 20 parts;
[0008] The polylactic acid satisfies: 2.8 ≤ X / D ≤ 22,
[0009] wherein, X is the content of terminal carboxyl groups in polylactic acid, mol KOH / t;
[0010] D is the polydispersity coefficient of polylactic acid.
[0011] The terminal carboxyl group in polylactic acid is one of the important structural units in the polylactic acid molecule. The presence of the terminal carboxyl group has an important impact on the physical and chemical properties of polylactic acid. It can catalyze the depolymerization or reverse reaction of the polylactic acid molecular chain, and will accelerate the aging and degradation of the material during material processing, storage and use. Its content depends on factors such as catalyst addition and polymerization reaction. By adjusting process parameters such as catalyst addition amount, reaction temperature and time, its value can be regulated; the polydispersity coefficient D of polylactic acid = Mw / Mn, where Mw and Mn are the weight-average molecular weight and number-average molecular weight of polylactic acid respectively. The polydispersity coefficient of polylactic acid is one of the important indicators for evaluating its dispersion performance. The polydispersity coefficient depends on the polymerization reaction mechanism. By adjusting process parameters such as reaction temperature, catalyst selection and its dosage, its value can be regulated.
[0012] The content of the terminal carboxyl group in polylactic acid, the polydispersity coefficient, its addition amount, the addition amount of talcum powder, and the addition amount of PBS jointly affect the moisture and heat aging resistance performance of the composite material. In the present invention, by adding a specific amount of talcum powder and PBS to polylactic acid and controlling the polylactic acid to satisfy 2.8 ≤ X / D ≤ 22, it has good moisture and heat aging resistance performance. For example, under the conditions of a temperature of 85°C and a humidity of 85%, after accelerating aging for 6 h, the tensile strength retention rate is greater than 60%.
[0013] The polylactic acid is 54 to 91 parts by weight, such as 54 parts by weight, 60 parts by weight, 65 parts by weight, 70 parts by weight, 75 parts by weight, 80 parts by weight, 85 parts by weight, 91 parts by weight or the range formed by any two of the above values. Preferably, the weight percentage content of the polylactic acid in the polylactic acid composite material is above 40%, such as 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 89.2% or the range formed by any two of the above values.
[0014] The talcum powder is 10 to 45 parts by weight, such as 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight, 45 parts by weight or the range formed by any two of the above values.
[0015] The PBS is 1 to 20 parts by weight, such as 1 part by weight, 3 parts by weight, 5 parts by weight, 7 parts by weight, 10 parts by weight, 12 parts by weight, 14 parts by weight, 16 parts by weight, 18 parts by weight, 20 parts by weight or the range formed by any two of the above values.
[0016] The X / D is 2.8 to 22, such as 3, 5, 7, 10, 12, 14, 16, 18, 20 or the range formed by any two of the above values.
[0017] Preferably, the weight percentage of magnesium oxide in the talcum powder is 20% - 45%. For example, the weight percentage of magnesium oxide in the talcum powder is 20%, 25%, 28%, 30%, 32%, 34%, 36%, 38%, 40%, 45% or any range formed by any two of the above values.
[0018] More preferably, the weight percentage of magnesium oxide in the talcum powder is 24% - 41%.
[0019] When the weight percentage of magnesium oxide in the talcum powder is in the range of 20% - 45%, especially in the range of 24% - 41%, the balance between the catalytic aging effect and the capping effect of magnesium oxide on polylactic acid can be better, and the moisture and heat aging resistance of the obtained polylactic acid composite material can be better.
[0020] The weight percentage of magnesium oxide in the talcum powder is measured according to the following test method: SNT 2949 - 2011 standard.
[0021] Preferably, the X is 5 - 35. For example, the X is 5, 8, 10, 12, 15, 18, 20, 22, 24, 26, 28, 30, 32, 35 or any range formed by any two of the above values.
[0022] The X is measured according to FZ / T 50012 - 2006 "Determination of Terminal Carboxyl Group Content in Polyester - Titrimetric Analysis Method". The weight ratio of o - cresol to chloroform in the used o - cresol - chloroform mixed solvent is 7:3, and the concentration of potassium hydroxide in the used potassium hydroxide - ethanol standard titration solution is 0.01 g / mL.
[0023] Preferably, the D is 1.2 - 2.5. For example, the D is 1.5 or any range formed by any two of the above values.
[0024] The D is tested by gel permeation chromatography (GPC). A tandem chromatographic column of KF803 and KF805 from SHODEX company is used. The temperature of the chromatographic system is 40°C, a refractive index detector is used, the eluent is chloroform, the eluent flow rate is 1 mL / min, and polystyrene is used as the reference standard.
[0025] Preferably, the melt flow rate of the polylactic acid under the conditions of 190 °C and a load of 2.16 kg is 3 to 30 g / 10 min. For example, the melt flow rate of the polylactic acid under the conditions of 190 °C and a load of 2.16 kg is 3 g / 10 min, 5 g / 10 min, 7 g / 10 min, 10 g / 10 min, 13 g / 10 min, 15 g / 10 min, 17 g / 10 min, 20 g / 10 min, 22 g / 10 min, 25 g / 10 min, 28 g / 10 min, 30 g / 10 min or any range formed by any two of the above values.
[0026] The melt flow rate of the polylactic acid is measured according to ISO 1133-1-2022.
[0027] The polylactic acid can be prepared by the following method: First, L-lactic acid and a first catalyst are mixed and then subjected to a polycondensation reaction to generate a lactide intermediate; then, the lactide intermediate, an initiator, and a second catalyst are mixed and subjected to a ring-opening polymerization reaction to generate a polylactic acid resin.
[0028] Among them, the first catalyst and the second catalyst in the above preparation method can each independently be a tin-based catalyst, specifically at least one of tin powder, tin oxide, or stannous octoate; the initiator can be ethylene glycol.
[0029] Optionally, the reaction temperature of the above polycondensation reaction is 80 to 140 °C, the reaction pressure is 3 to 8 KPa, and the reaction time is 6 to 12 h. After the polycondensation reaction, the oligomers generated by the polycondensation reaction can be subjected to vacuum distillation until no product distills out to obtain a lactide intermediate; the conditions for vacuum distillation include: a temperature of 170 to 210 °C, a pressure of 102 to 103 Pa, and a time of 7 to 15 h.
[0030] Optionally, the above ring-opening polymerization reaction includes two stages. The conditions for the first stage include: a reaction temperature of 140 to 160 °C, a reaction pressure of 105000 to 115000 Pa, and a reaction time of 3 to 5 h; the conditions for the second stage include: a reaction temperature of 170 to 190 °C, a reaction pressure of 105000 to 115000 Pa, and a reaction time of 2 to 3 h. In the ring-opening polymerization reaction, the polymer generated by the ring-opening polymerization reaction can be dissolved in a chloroform aqueous solution and then precipitated with ethanol to obtain a polylactic acid resin.
[0031] Preferably, the average particle size D90 of the talcum powder satisfies 3 μm ≤ D90 ≤ 25 μm. For example, the average particle size D90 of the talcum powder is 3 μm, 5 μm, 7 μm, 10 μm, 12 μm, 15 μm, 17 μm, 20 μm, 22 μm, 25 μm or any range formed by any two of the above values.
[0032] The average particle size of the talcum powder is obtained by testing with a laser particle size analyzer according to Standard GB / T 19077-2016.
[0033] Preferably, the melt flow rate of the polybutylene succinate under the conditions of 190 °C and a load of 2.16 kg is 3-20 g / 10 min, such as 3 g / 10 min, 5 g / 10 min, 7 g / 10 min, 10 g / 10 min, 13 g / 10 min, 15 g / 10 min, 17 g / 10 min, 20 g / 10 min or the range formed by any two of the above values.
[0034] The melt flow rate of the polybutylene succinate is measured according to ISO 1133-1-2022.
[0035] The polylactic acid composite material may further comprise the following components in parts by weight: 0-2 parts of additives (such as 0 part by weight, 0.05 part by weight, 1 part by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight, 1.8 parts by weight, 2 parts by weight or the range formed by any two of the above values). The additives may optionally include at least one of an antioxidant, a light stabilizer, and a lubricant. Exemplarily, the antioxidant includes at least one of a hindered phenol antioxidant or a phosphite; the light stabilizer includes at least one of a hindered amine light stabilizer or a benzotriazole light stabilizer; the lubricant includes at least one of an amide lubricant or an ester lubricant.
[0036] In a second aspect, the present application provides a method for preparing the polylactic acid composite material, comprising the following steps:
[0037] Mix and disperse all the raw materials, melt extrude, and pelletize to obtain the polylactic acid composite material.
[0038] Preferably, the temperature of the melt extrusion is 140-240 °C.
[0039] In a third aspect, the present application further provides the application of the polylactic acid composite material in tableware. For example, it can be used to prepare knives, forks, spoons, straws, dinner plates, etc.
[0040] Compared with the prior art, the beneficial effects of the present application are as follows: By adding a specific amount of talcum powder and PBS to polylactic acid and controlling the content of the terminal carboxyl group and the polydispersity coefficient of polylactic acid to satisfy a specific relationship, the obtained polylactic acid composite material is ensured to have good resistance to wet and heat aging performance. For example, the tensile strength retention rate is greater than 60% after 6 h of accelerated aging under the conditions of a temperature of 85 °C and a humidity of 85%. It is suitable as a product material with relatively high requirements for resistance to wet and heat aging, such as extrusion grade or injection molding grade. For example, it can be used to prepare tableware such as knives, forks, spoons, straws, dinner plates, etc. Detailed embodiments
[0041] To better illustrate the purpose, technical solution and advantages of the present application, the present application will be further described below in conjunction with specific examples and comparative examples. The purpose is to understand the content of the present application in detail, rather than a limitation to the present application. All other examples obtained by those of ordinary skill in the art without creative efforts fall within the protection scope of the present application. The experimental reagents and instruments involved in the implementation of the present application are all common ordinary reagents and instruments unless otherwise specified. In the present application, among the technically characterized described in an open-ended manner, it includes a closed technical solution composed of the listed characteristics, and also includes an open technical solution containing the listed characteristics.
[0042] The following examples and comparative examples each provide a polylactic acid composite material. The formulations of these polylactic acid composite materials are shown in Tables 2 and 3, and their preparation methods include the following steps: Mix and disperse all raw materials and then feed them into a twin-screw extruder, melt extrude, and granulate to obtain the polylactic acid composite material;
[0043] Among them, the length-diameter ratio of the screw of the twin-screw extruder is 40:1, the screw rotation speed is 350 - 450 r / min, and the melt extrusion temperature is 160 - 210 °C.
[0044] The raw material information used in the above examples and comparative examples is as follows, and unless otherwise specified, they are all commercially available raw materials. In addition, the component raw materials used in each parallel experiment are all of the same kind:
[0045] (1) PLA
[0046] PLA is self-made, and the preparation method is as follows:
[0047] First, mix L-lactic acid and the first catalyst and then carry out a polycondensation reaction to generate a lactide intermediate; then mix the lactide intermediate, initiator and the second catalyst and carry out a ring-opening polymerization reaction to generate a polylactic acid resin.
[0048] Among them, at least one of the first catalyst and the second catalyst in the above preparation method is tin oxide; the initiator is ethylene glycol.
[0049] The reaction temperature of the above polycondensation reaction is 80 - 140 °C, the reaction pressure is 3 - 8 KPa, and the reaction time is 6 - 12 h. After the polycondensation reaction, the oligomers generated by the polycondensation reaction are subjected to vacuum distillation until no product distillate is obtained to obtain the lactide intermediate; the conditions for vacuum distillation include: temperature of 170 - 210 °C, pressure of 102 - 103 Pa, and time of 7 - 15 h.
[0050] The above ring-opening polymerization reaction includes two stages. The conditions of the first stage include: the reaction temperature is 140 - 160 °C, the reaction pressure is 105000 - 115000 Pa, and the reaction time is 3 - 5 h; the conditions of the second stage include: the reaction temperature is 170 - 190 °C, the reaction pressure is 105000 - 115000 Pa, and the reaction time is 2 - 3 h. In the ring-opening polymerization reaction, the polymer generated by the ring-opening polymerization reaction is dissolved in an aqueous chloroform solution and then precipitated with ethanol to obtain a polylactic acid resin.
[0051] The value of the content X of the terminal carboxyl group in PLA is regulated by controlling the reaction temperature, and the value of the polydispersity coefficient of PLA is regulated by controlling the reaction temperature, the type and dosage of the catalyst, and the melt flow rate of PLA is regulated by controlling the reaction temperature, the type and dosage of the catalyst.
[0052] The X, D of PLA - 1 to PLA - 9 and the melt flow rate under the conditions of 190 °C and a load of 2.16 kg are shown in Table 1.
[0053] Table 1
[0054]
[0055]
[0056] (2) Talc
[0057] Talc - 1: The weight percentage of magnesium oxide is 30%, the average particle size is 8 μm, and it is obtained by screening with SD - 9449 of Liaoning Xinda;
[0058] Talc - 2: The weight percentage of magnesium oxide is 25%, the average particle size is 8 μm, and it is obtained by screening with SD - 9446 of Liaoning Xinda;
[0059] Talc - 3: The weight percentage of magnesium oxide is 40%, the average particle size is 8 μm, and it is obtained by screening with SD - 9462 of Liaoning Xinda;
[0060] Talc - 4: The weight percentage of magnesium oxide is 20%, the average particle size is 8 μm, and it is obtained by screening with SD - 9440 of Liaoning Xinda;
[0061] Talc - 5: The weight percentage of magnesium oxide is 45%, the average particle size is 8 μm, manufacturer Liaoning Xinda, model SD - 9445.
[0062] (3) PBS
[0063] The melt flow rate under the conditions of 190 °C and a load of 2.16 kg is 4 g / 10 min, model A200NC801, manufacturer Zhuhai Jinfabio.
[0064] (4) Auxiliary agent
[0065] The hindered phenol antioxidant, RIANOX 1010, is commercially available.
[0066] The following performance tests were carried out on the polylactic acid composite materials of the above examples and comparative examples:
[0067] The polylactic acid composite material samples were randomly divided into group A and group B. Among them, group A was directly tested according to the method specified in GB / T 1040.2-2022 "Determination of tensile properties of plastics - Part 2: Test conditions for moulding and extrusion plastics" at a tensile rate of 50 mm / min under condition 1A, and the tensile strength I was measured; group B was placed at a temperature of 85 °C and a humidity of 85% for 6 h, and then the tensile strength was tested according to the above method, and the tensile strength II was measured; the tensile strength retention rate (%) = tensile strength II / tensile strength I × 100%.
[0068] The test results are shown in Tables 2 and 3.
[0069] Table 2
[0070]
[0071]
[0072] Table 3
[0073]
[0074] From the above data, it can be seen that the polylactic acid composite materials of each example of the present application have excellent resistance to heat and humidity aging performance. For example, after aging at a temperature of 85 °C and a humidity of 85% for 6 h, the tensile strength retention rate is above 60%.
[0075] Compared with Examples 1-6, the X / D values of the PLA used in Comparative Examples 1-2 are too small or too large, resulting in poor resistance to heat and humidity aging performance of the obtained composite materials. It can be seen that it is necessary to control the X / D value of PLA within the range of 3-20 to ensure that the composite material has excellent resistance to heat and humidity aging performance.
[0076] Comparing Examples 1-3 with Comparative Examples 3-4, it can be seen that adding an appropriate amount of PBS is beneficial to improving the balance of the heat resistance and hydrolysis resistance of the composite material, thereby making its resistance to heat and humidity aging performance better; in Comparative Examples 3-4, PBS was not added or the added PBS was excessive, breaking the balance relationship between the heat resistance and hydrolysis resistance of the composite material, and making its resistance to heat and humidity aging performance poor. Comparing Example 1 with Examples 10-13, it can be seen that when the weight percentage content of magnesium oxide in talc is within the range of 24% - 41%, the obtained composite material has significantly better resistance to heat and humidity aging performance.
[0077] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application rather than to limit the protection scope of the present application. Although the present application has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present application can be modified or equivalently replaced without departing from the essence and scope of the technical solutions of the present application.
Claims
1. A polylactic acid composite material, characterized in that, Comprising the following components in parts by weight: 54 - 91 parts of polylactic acid, 10 - 45 parts of talcum powder, 1 - 20 parts of polybutylene succinate; The polylactic acid satisfies: 2.8 ≤ X / D ≤ 22, wherein, X is the content of terminal carboxyl groups in polylactic acid, mol KOH / t; D is the polydispersity coefficient of polylactic acid.
2. The polylactic acid composite material according to claim 1, characterized in that The weight percentage content of magnesium oxide in the talcum powder is 20% - 45%, preferably 24% - 41%.
3. The polylactic acid composite material according to claim 1, wherein The X is 5 - 35.
4. The polylactic acid composite material according to claim 1, wherein The D is 1.2 - 2.
5.
5. The polylactic acid composite material according to claim 1, wherein The melt flow rate of the polylactic acid under the conditions of 190°C and a load of 2.16 kg is 3 - 30 g / 10 min.
6. The polylactic acid composite material according to claim 1, wherein The average particle size D90 of the talcum powder satisfies 3 μm ≤ D90 ≤ 25 μm.
7. The polylactic acid composite material according to claim 1, wherein The melt flow rate of the polybutylene succinate under the conditions of 190°C and a load of 2.16 kg is 3 - 20 g / 10 min.
8. The preparation method of the polylactic acid composite material according to any one of claims 1 to 7, characterized in that, Including the following steps: mixing and dispersing all raw materials, melt - extruding, and pelletizing to obtain a polylactic acid composite material.
9. The preparation method of the polylactic acid composite material according to claim 8, characterized in that, The temperature of the melt - extrusion is 140 - 240°C.
10. Use of the polylactic acid composite material according to any one of claims 1 - 7 in tableware.